DIAGNOSIS IMPLICATIONS IN PREVENTING ORAL FUNCTIONAL DECLINE - Dragos Nicolae Fratila; Dana Gabriela Budala; Florinel Cosmin Bida; Ionut Luchian; Monica Mihaela Scutariu; Dragos Ioan Virvescu; Zenovia Surlari (Romanian Dental Association for Education, 2023)
Oral health is essential to human health. conditions associated with poor oral health involve all organ systems and many major disease categories including infectious disease, cardiovascular disease, chronic pain, cancer, and mental health. outcomes are also associated with health equity. The oral cavity functions in eating, speaking, socializing, and serving as a natural barrier to external pathogens. In the prevention of oral function decline in older people, oral health conditions should be maintained through public health actions.